Exploring the co-loading of lidocaine chemical forms in surfactant/phospholipid vesicles for improved skin delivery. (3rd February 2015) - Caddeo, Carla; Valenti, Donatella; Nácher, Amparo; Manconi, Maria; Fadda, Anna Maria
Abstract: Objectives: The present study was aimed at targeting the skin to deliver lidocaine loaded in surfactant/phospholipid vesicles tailored for improved local delivery. The influence of different formulation parameters was explored to maximise drug efficacy. Methods: The vesicles were prepared using a mixture of soy lipids (Phospholipon 50) and a surfactant with penetration-enhancing properties (Oramix CG110, Labrasol, Labrafac PG or Labrafac CC), and loaded with lidocaine. The formulations were analysed in detail by cryo-TEM, SAXS, Turbiscan Lab, and tested in permeation experiments through new born pig skin, as a function of the chemical form and concentration of lidocaine (i.e. free base or salt, 12.5 or 25 mg/ml). Key findings: Small, spherical vesicles with good entrapment efficiency and exceptional long-term stability were produced. The lamellar organisation was affected by either the surfactant or the lidocaine form used. Permeation studies highlighted that the co-incorporation of lidocaine base + hydrochloride allowed the achievement of a superior deposition in the skin layers, especially when surfactant vesicles were used, as their content was presumably saturated with the maximum amount of loadable anaesthetic. Conclusions: The proposed systems based on surfactant/phospholipid vesicles co-loaded with both lidocaine forms are an effective approach for improving its local delivery.